This is service design doing : applying service design thinking in the real world: a practitioners' handbook - Stickdorn, Marc, ....-; Lawrence, Adam, ....-; Hormess, Markus, ....-; Schneider, Jakob, ....- (Sebastopol : O'Reilly Media Inc., 2018)
"How can you establish a customer-centric culture in an organization? This is the first comprehensive book on how to actually do service design to improve the quality and the interaction between service providers and customers. You'll learn specific facilitation guidelines on how to run workshops, perform all of the main service design methods, implement concepts in reality, and embed service design successfully in an organization. Great customer experience needs a common language across disciplines to break down silos within an organization. This book provides a consistent model for accomplishing this and offers hands-on descriptions of every single step, tool, and method used.You'll be able to focus on your customers and iteratively improve their experience. Move from theory to practice and build sustainable business success."
Keywords: Consumentengedrag; Organisatieleer